The Effect of Group Counselling based on Mindfulness on the Perceived Stress of Pregnant Women with Gestational Diabetes Referring to the Comprehensive Health Service and Diabetes Center in Hamadan City in 2021: A Randomized Controlled Clinical Trial Study - Anajafi, Niloofar; Masoumi, Seyedeh Zahra; Kazemi, Farideh; Aghababaei, Soodabeh; Ahmadpanah, Mohammad; Jenabi, Ensiyeh (Reviews on Recent Clinical Trials, 2025)
<span class=
Keywords: Group counselling